Bone quantitative susceptibility mapping using a chemical species–specific R2* signal model with ultrashort and conventional echo data. Issue 1 (5th March 2017) - Dimov, Alexey V.; Liu, Zhe; Spincemaille, Pascal; Prince, Martin R.; Du, Jiang; Wang, Yi
Abstract : Purpose: To develop quantitative susceptibility mapping (QSM) of bone using an ultrashort echo time (UTE) gradient echo (GRE) sequence for signal acquisition and a bone‐specific effective transverse relaxation rate ( R 2 * ) to model water–fat MR signals for field mapping. Methods: Three‐dimensional radial UTE data (echo times ≥ 40 μs) was acquired on a 3 Tesla scanner and fitted with a bone‐specific signal model to map the chemical species and susceptibility field. Experiments were performed ex vivo on a porcine hoof and in vivo on healthy human subjects (n = 7). For water–fat separation, a bone‐specific model assigning R 2 * decay mostly to water was compared with the standard models that assigned the same decay for both fat and water. In the ex vivo experiment, bone QSM was correlated with CT. Results: Compared with standard models, the bone‐specific R 2 * method significantly reduced errors in the fat fraction within the cortical bone in all tested data sets, leading to reduced artifacts in QSM. Good correlation was found between bone CT and QSM values in the porcine hoof (R 2  = 0.77). Bone QSM was successfully generated in all subjects. Conclusions: The QSM of bone is feasible using UTE with a conventional echo time GRE acquisition and a bone‐specific R 2 * signal model. Magn Reson Med 79:121–128, 2018. © 2017 International Society for Magnetic Resonance in Medicine.